2021
DOI: 10.1136/jitc-2021-003195
|View full text |Cite
|
Sign up to set email alerts
|

Virological breakthrough after immune checkpoint inhibitor and nucleos(t)ide analog treatment in patients with hepatitis B surface antigen positive hepatocellular carcinoma: a real-world study

Abstract: BackgroundImmune checkpoint inhibitors (ICIs) have been shown to be a promising and effective treatment for hepatitis B virus (HBV)-related hepatocellular carcinoma (HCC). However, there is a lack of evidence-based data demonstrating the impact of ICIs on HBV DNA level in HBV-HCC patients undergoing nucleos(t)ide analog (NA) therapy and of HBV DNA variation on patient survival. In this study, we aimed to investigate this issue in the real world.MethodsIn this single-center retrospective study, we reviewed 182 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 46 publications
(41 reference statements)
0
1
0
Order By: Relevance
“…At present, the precise mechanism of HBV re-replication or reactivation in patients treated with PD-1/PD-L1 antibodies is unknown. In a recent study, researchers reported that virological breakthrough(VB) was an indicator of poor outcome in patients with HBsAg positive HCC under ICIs therapy ( 54 ). This finding is similar with our study.…”
Section: Discussionmentioning
confidence: 99%
“…At present, the precise mechanism of HBV re-replication or reactivation in patients treated with PD-1/PD-L1 antibodies is unknown. In a recent study, researchers reported that virological breakthrough(VB) was an indicator of poor outcome in patients with HBsAg positive HCC under ICIs therapy ( 54 ). This finding is similar with our study.…”
Section: Discussionmentioning
confidence: 99%